Direct reprogramming of fibroblasts into renal tubular epithelial cells by defined transcription factors - Kaminski, Michael M.; Tosic, Jelena; Kresbach, Catena; Engel, Hannes; Klockenbusch, Jonas; Müller, Anna-Lena; Pichler, Roman; Grahammer, Florian; Kretz, Oliver; Huber, Tobias B.; Walz, Gerd; Arnold, Sebastian J.; et al. (Nature cell biology, 2016)
Direct reprogramming by forced expression of transcription factors can convert one cell type into another. Thus, desired cell types can be generated bypassing pluripotency. However, direct reprogramming towards renal cells remains an unmet challenge. Here, we identify renal cell fate-inducing factors on the basis of their tissue specificity and evolutionarily conserved expression, and demonstrate that combined expression of Emx2 , Hnf1b , Hnf4a and Pax8 converts mouse and human fibroblasts into induced renal tubular epithelial cells (iRECs). iRECs exhibit epithelial features, a global gene expression profile resembling their native counterparts, functional properties of differentiated renal tubule cells and sensitivity to nephrotoxic substances. Furthermore, iRECs integrate into kidney organoids and form tubules in decellularized kidneys. Our approach demonstrates that reprogramming factors can be identified by targeted in silico analysis. Renal tubular epithelial cells generated ex vivo by forced expression of transcription factors may facilitate disease modelling, drug and nephrotoxicity testing, and regenerative approaches. Kaminski et al. demonstrate that combined expression of the transcription factors Emx2, Hnf1b, Hnf4a and Pax8 converts mouse and human fibroblasts into induced renal tubular epithelial cells.